The effect of H2O and PEG on the morphologies of ZnO nanostructures synthesized under microwave radiation - Thongtem T. (2014)
ZnO nanoparticles and nanorods were synthesized from Zn(NO3)2·6H2O and NaOH in H2O and in different molecular weights (MWs) of polyethylene glycol (PEG) using 180 W microwave radiation. The phase was detected using X-ray diffraction (XRD) and selected area electron diffraction (SAED). The diffraction pattern was in accordance with that obtained by simulation. Scanning and transmission electron microscopy (SEM and TEM) revealed the presence of nanoparticles with an average size of 12.7 ± 2.7 nm in water; these gradually changed into nanorods in PEG with different MWs. Four Raman vibrations were detected, with the strongest intensity at 439 cm-1, specified as the optical phonon E2H high frequency mode. Luminescence emission was detected at 366-374 nm, caused by the recombination of free excitons in the products. Emission intensity was highest for the product synthesized in PEG600. © 2009 Elsevier B.V. All rights reserved.